Foodborne infections and food safety - Bhattacharyya, Sayan; Das, Chhandasi (Eastern Journal of Medical Sciences, 2022)
Foodborne infections are very serious and pose a serious public health challenge, especially in the tropical countries. Toxins produced by microorganisms can lead to watery diarrhea, loose stool, or invasive diarrhea. Some proper safety practices and norms can help mitigate foodborne infections to a large extent. One needs to be vigilant and aware of food hygiene and this can help in preventing microbiological contamination in food.